PENGARUH PERTUMBUHAN KREDIT, DANA PIHAK KETIGA, DAN APLIKASI SISTEM INFORMASI AKUNTANSI PADA KINERJA OPERASIONAL - Bayu Andhika, Putu; Sujana, I Ketut (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of credit growth, third-party funds, and accounting information system applications on operating performance LPD In Badung 2011-2013, The number of samples of this study was 78 LPD in Badung use probability sampling method with the formula slovin. Data collection was done by using non-participant observation. The data analysis technique used this research is multiple linear regression analysis. The results showed that (1) credit growth positive effect on operating performance , (2) growth of deposits positive effect on operating performance, (3) the growth of savings positive effect on operating performance, (4) the application of accounting information system has positive influence on operational performance
Keywords: Growth in Loans, Deposits, Application of Accounting Information Systems, and Operational Performance